Delamination Behaviour of Embedded Polymeric Sensor and Actuator Carrier Layers in Epoxy Based CFRP Laminates—A Study of Energy Release Rates - Andreas Hornig (MDPI AG, 2021)
Fiber reinforced composites combine low density with high specific mechanical properties and thus became indispensable for today’s lightweight applications. In particular, carbon fibre reinforced plastic (CFRP) is broadly used for aerospace components. However, damage and failure behaviour, especially for complex fibre reinforcement set-ups and under impact loading conditions, are still not fully understood yet. Therefore, relatively large margins of safety are currently used for designing high-performance materials and structures. Technologies to functionalise the materials enabling the monitoring of the structures and thus avoiding critical conditions are considered to be key to overcoming these drawbacks. For this, sensors and actuators are bonded to the surface of the composite structures or are integrated into the composite lay-up. In case of integration, the impact on the mechanical properties of the composite materials needs to be understood in detail. Additional elements may disturb the composite structure, impeding the direct connection of the composite layers and implying the risk of reducing the interlaminar integrity by means of a lower delamination resistance. In the presented study, the possibility of adjusting the interface between the integrated actuator and sensor layers to the composite layers is investigated. Different polymer layer combinations integrated into carbon fibre reinforced composite layups are compared with respect to their interlaminar critical energy release rates <semantics>GIc</semantics> and <semantics>GIIc</semantics>. A standard aerospace unidirectionally reinforced (UD) CFRP prepreg material was used as reference material configuration. The investigations show that it is possible to enhance the mechanical properties, especially the interlaminar energy release rate by using multilayered sensor–actuator layers with Polyimide (PI) outer layers and layers with low shear stiffness in between.